Rola nauczyciela w nauczaniu języków specjalistycznych - Sierocka, Halina (The Role of the ESP Teacher, 2008)
This paper aims to discuss the role of the ESP (English for Special Purposes) teacher - how it is different from teaching general English and what problems ESP teachers may encounter at their work. Firstly some basic concepts of ESP like its development and definition are presented, then different roles of the teacher in ESP classes are explored further. Finally, the author deals with some issues hindering the ESP teacher's work. i.e. lack of tradition, lack of specialist knowledge or lack of teaching materials.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 202-208